Down comes the rain - Branley, Franklyn Mansfield, 1915-2002.; Hale, James Graham (New York : HarperCollins, 1997)
Explains how the water cycle leads to different types of weather patterns.
Wilson's Children, October 2010.
Elem. School Library Collection, June 2000.
School Library Journal, October 1997.
Science Books & Films (A.A.A.S.), January 1998.
L.A. Recommended Foreign Language, February 1999.
Wilson's Children.
Keywords: Rain and rainfall -- Juvenile literature; Clouds -- Juvenile literature; Rain and rainfall; Clouds; Rain; Clouds; Rain and rainfall; Clouds